Identification of site-specific adaptations conferring increased neural cell tropism during human enterovirus 71 infection. - Samuel Cordey; Tom J Petty; Manuel Schibler; Yannick Martinez; Daniel Gerlach; Sandra van Belle; Lara Turin; Evgeny Zdobnov; Laurent Kaiser; Caroline Tapparel (PLoS Pathogens)
Enterovirus 71 (EV71) is one of the most virulent enteroviruses, but the specific molecular features that enhance its ability to disseminate in humans remain unknown. We analyzed the genomic features of EV71 in an immunocompromised host with disseminated disease according to the different sites of infection. Comparison of five full-length genomes sequenced directly from respiratory, gastrointestinal, nervous system, and blood specimens revealed three nucleotide changes that occurred within a five-day period: a non-conservative amino acid change in VP1 located within the BC loop (L97R), a region considered as an immunogenic site and possibly important in poliovirus host adaptation; a conservative amino acid substitution in protein 2B (A38V); and a silent mutation in protein 3D (L175). Infectious clones were constructed using both BrCr (lineage A) and the clinical strain (lineage C) backgrounds containing either one or both non-synonymous mutations. In vitro cell tropism and competition assays revealed that the VP1₉₇ Leu to Arg substitution within the BC loop conferred a replicative advantage in SH-SY5Y cells of neuroblastoma origin. Interestingly, this mutation was frequently associated in vitro with a second non-conservative mutation (E167G or E167A) in the VP1 EF loop in neuroblastoma cells. Comparative models of these EV71 VP1 variants were built to determine how the substitutions might affect VP1 structure and/or interactions with host cells and suggest that, while no significant structural changes were observed, the substitutions may alter interactions with host cell receptors. Taken together, our results show that the VP1 BC loop region of EV71 plays a critical role in cell tropism independent of EV71 lineage and, thus, may have contributed to dissemination and neurotropism in the immunocompromised patient.